SCF(Fbw7) Regulates Cellular Apoptosis By Targeting Mcl-1 for Ubiquitination and Destruction - Inuzuka, Hiroyuki (2011)
The effective use of targeted therapy is highly dependent upon the identification of responder patient populations. Loss of the Fbw7 tumor suppressor is frequently found in various types of human cancers including breast cancer, colon cancer 1 and T-cell acute lymphoblastic leukemia (T-ALL)2. In line with these genomic data, engineered deletion of Fbw7 in mouse T cells results in T-ALL3–5, validating Fbw7 as a T-ALL tumor suppressor. The precise molecular mechanisms by which Fbw7 exerts anti-tumor activity remain areas of intensive investigation and are thought to relate in part to Fbw7-mediated destruction of key cancer relevant proteins including c-Jun6, c-Myc 7, Cyclin E 8 and Notch-19, all of which possess oncogenic activity and are overexpressed in various human cancers including leukemia. Besides accelerating cell growth 10, overexpression of either c-Jun, c-Myc or Notch-1 can also provoke programmed cell death 11. Thus, considerable uncertainty surrounds how Fbw7-deficient cells evade cell death in the setting of upregulated c-Jun, c-Myc and/or Notch-1. Here we report that SCF(Fbw7) governs cellular apoptosis by targeting the pro-survival Bcl-2 family member, Mcl-1, for ubiquitination and destruction in a GSK3 phosphorylation-dependent manner. Human T-ALL cell lines showed a close relationship between Fbw7 loss and Mcl-1 overexpression. Correspondingly, T-ALL cell lines with defective Fbw7 are particularly sensitive to the multi-kinase inhibitor, sorafenib, but resistant to the Bcl-2 antagonist, ABT-737. On the genetic level, Fbw7 reconstitution or Mcl-1 depletion restores ABT-737 sensitivity, establishing Mcl-1 as a therapeutically relevant bypass survival mechanism for Fbw7-deficient cells to evade apoptosis. Therefore, our work provides novel molecular insight into Fbw7-direct tumor suppression with direct implications for the targeted treatment of Fbw7-deficient T-ALL patients.